Comparative analysis of the push-out bond strength of fiber posts: Immediate vs. delayed post-space preparation with two obturation techniques - Weilin Long; Xiongjun Xu; Li Tang; Hongwei Jiang; Yihua Huang (PLoS ONE, 2025)
Objectives The objective of this study was to assess the impact of immediate and delayed post- space preparation on the push-out bond strength (PBS) of fiber posts by employing two root canal obturation techniques: continuous wave of condensation (CWC) and single-cone (SC) obturation. Materials and methods Forty-eight human maxillary premolar teeth were instrumented, and the samples were divided into four groups according to the obturation technique and the time of post-space preparation. SC and CWC underwent immediate post-space preparation; and CWC and SC underwent delayed post-space preparation. The smear layer and dentine tubules from the apical, middle, and cervical regions of the samples were observed via scanning electron microscopy (SEM) and the %VoidsVol of the medium 4-mm fiber posts of each group was calculated via micro-computed tomography (CT). Each post space of the root was subsequently cut into slices, resulting in three 1-mm slices at 3 different depths (apical to the cervical region) and subjected to a push-out test. The failure mode was assessed. The data were analysed via the Shapiro-Wilk test, one-way analysis of variance and Bonferroni correction tests. Results In terms of depth from the apical to the cervical region, SC following immediate post-space preparation exhibited greater bond strength than did CWC following delayed post-space preparation. SEM images revealed that the smear layer was completely visible. In the SC with immediate post-space preparation group, the smear layer could be partially removed from the apical, middle and cervical regions of the samples and the outlines of the dentine tubules were visible. The percentage volume of the voids of the medium 4-mm fiber posts of the four groups and the samples in the three directions were not significantly different. No significant differences were observed in the CWC or SC obturation technique regardless of the time of post-space preparation or in immediate or delayed post-space preparation with different obturation techniques. Conclusions SC followed by immediate post-space preparation provided better bond strength of fiber posts to intraradicular dentine than did CWC followed by delayed post-space preparation.